The Psychological Factors in Arabic Language Acquisition of Modern Islamic Boarding School Students - Sutarjo, J (Arabiyatuna: Jurnal Bahasa Arab, 2025)
This study aimed to describe an Islamic boarding school in Indonesia that taught Arabic with both divine and active competence. Specifically, this study examined: (1) the Arabic language learning process, (2) the Arabic language acquisition process, and (3) the relevance of acquisition theory from a psycholinguistic perspective to the Arabic language learning process. The research was conducted at Madina Islamic Boarding School, located in Karya Tani, Labuhan Meringgai, East Lampung, Indonesia. Various aspects supported the success of this institution in implementing and developing Arabic language learning. Hence, it was intriguing to investigate the language acquisition process of the students at this school. This research was field-based, with data collected through observation, interviews, and documentation methods. The data were analyzed qualitatively. The findings revealed that Arabic language learning took place inside and outside the classroom. Students’ Arabic language acquisition occurred in both settings and was influenced by several aspects, including psychological factors.